Africa?s health challenges sovereignty, mobility of people and healthcare governance (Farnham Burlington, 2013)
This volume addresses the ideational and policy-oriented challenges of Africa's health governance due to voluntary and involuntary cross-border migration of people and diseases in a growing 'mobile Africa'. The collected set of specialized contributions in this volume examines how national and regional policy innovation can address the competing conception of sovereignty in dealing with Africa's emerging healthcare problems in a fast-paced, interconnect world.
Includes bibliographical references (pages [215]-243) and index.
Keywords: Public health --Africa.